2015
DOI: 10.1371/journal.pone.0124889
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Toceranib/Piroxicam/Cyclophosphamide Maintenance Therapy on Outcome of Dogs with Appendicular Osteosarcoma following Amputation and Carboplatin Chemotherapy: A Multi-Institutional Study

Abstract: BackgroundWe hypothesized that the addition of toceranib to metronomic cyclophosphamide/piroxicam therapy would significantly improve disease-free interval (DFI) and overall survival (OS) in dogs with appendicular osteosarcoma (OSA) following amputation and carboplatin chemotherapy.Methods and FindingsThis was a randomized, prospective clinical trial in which dogs with OSA free of gross metastatic disease (n = 126) received carboplatin chemotherapy (4 doses) following amputation. On study entry, dogs were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 57 publications
3
43
2
Order By: Relevance
“…Today, clear indications for using TOC in canine OS treatment are not available, and recent clinical trials did not support the use of TOC as a single agent or in combination with other commonly used therapies . In conclusion, our results demonstrate that TOC is able to mildly inhibit cell growth in vitro, while its effect is more relevant in xenograft models.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Today, clear indications for using TOC in canine OS treatment are not available, and recent clinical trials did not support the use of TOC as a single agent or in combination with other commonly used therapies . In conclusion, our results demonstrate that TOC is able to mildly inhibit cell growth in vitro, while its effect is more relevant in xenograft models.…”
Section: Discussioncontrasting
confidence: 56%
“…However, there is increasing evidence that other solid tumours, such as anal sac, head‐neck and thyroid carcinomas, and OSA can be successfully treated with TOC . Clinical trials performed on canine OSA patients showed controversial results when using Palladia as a single agent in canine metastatic OSA or in combination with other drugs, suggesting that more data are needed to clarify its benefit . Xenograft mouse models represent important tools for investigating the in vivo response to cancer therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Metronomic chemotherapy is the administration of daily or every other day low-dose alkylating agents in combination with NSAIDs and has been evaluated in both the adjunctive and gross disease setting for various canine and feline neoplasms (Lana and others 2007, Burton and others 2011, Tripp and others 2011, Marchetti and others 2012, Leo and others 2014, London and others 2015). …”
Section: Chemotherapymentioning
confidence: 99%
“…However, other studies have failed to show a clear clinical benefit. A randomized, prospective clinical trial of dogs with appendicular osteosarcoma in which dogs received metronomic cyclophosphamide/piroxicam with or without toceranib following standard of care therapy (amputation and carboplatin chemotherapy) found no significant difference in disease‐free interval, OS or 1‐year survival rate . In a subsequent pilot study, a similar conclusion was reached and toceranib alone following amputation and carboplatin yielded a median survival of 253 days in 10 dogs .…”
Section: Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 84%